Eco-Philosophy sebagai Cetak Biru Filsafat Ramah Lingkungan - Supian Supian (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2014)
This article proves that there is a significant relationship between the Islamic philosophy along with spiritual ecology and the ecological crisis and its solution. Loss of views and beliefs of spiritual ecology are among causes of environmental damage and the universe. Therefore, the restoration of spiritual ecology and its relationship to ecological values will play a pivotal role in the conservation and rescuing of natural and environmental crisis. Spiritual and Islamic philosophical values have ecological implications and consequences that should be the attitude and lifestyle in creating a harmonious relationship between God, man, and the universe. Eco-philosophy presents what so-called the values of spirituality as its base and emphasizes that humans remain to be special from other creatures. However, such privilege has to be a burden for humans and they are obliged to maintain and preserve the universe with spirituality and based on cosmic theology as coined in Islamic philosophy. Keywords: eco-philosophy, ecological crisis, spiritual ecology, cosmic teleology.